Video games and Kahoot! as cognitive gamifiers in compulsory social isolation - Alanya Beltran, Joel Elvys (2020)
Current educational gamifiers are based on the application of semi-formal and non-formal platforms to lead to more flexible learning in the current pandemic context. Given this, we propose the objective of investigating teaching and stimulating the learning of mathematical competencies in two Latin American contexts. We included in the first study 142 professors from the São Paulo Government of Brazil to study the use of the game through an evaluation by Kahoot! In another phase, we included 257 Basic Education teachers and 1,456 students from Peru to develop an experiment with non-serious video games. The conclusions allow us to argue that a large part of the teachers accept the Kahoot! Platform as an evaluating and gamifying means with equal effects to the use of traditional games in current education. Similarly, video games develop numerical thinking and mathematical reasoning in students who receive a virtual education in pandemic contexts. The contributions of the study also invite to introduce gamifiers as attitudinal increasing elements of complex learning in the classroom.